2011
DOI: 10.1002/cyto.a.21050
|View full text |Cite
|
Sign up to set email alerts
|

Both CD62 and CD162 antibodies prevent formation of CD36‐dependent platelets, rosettes, and artefactual pseudoexpression of platelet markers on white blood cells: A study with ImageStream®

Abstract: Fluorescent labeled monoclonal antibodies (mAbs) against CD36 are routinely used as monocyte, erythroid, or platelet markers in clinical cytometry. CD36 has recently been proposed by various authors as a valuable marker helping to enumerate leukocyte's subpopulations by flow cytometry. However, it is known that binding of CD36 may induce platelet activation and formation of platelet's rosettes on leukocytes, resulting in false expression of platelet markers on white blood cells. To study this phenomenon, we ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 21 publications
(27 reference statements)
1
20
0
Order By: Relevance
“…The percentage of neutrophils with adherent platelets decreased from 64 to 3% in the presence of the anti-CD162 mAb, ranging from 1 to 3 particles per FITC-fluorescent cells [22]. These observations suggest that MIFC can be a useful tool to study in depth the formation of cell aggregates, and their constituents.…”
Section: Multi-cell Clustering and Aggregatesmentioning
confidence: 82%
See 2 more Smart Citations
“…The percentage of neutrophils with adherent platelets decreased from 64 to 3% in the presence of the anti-CD162 mAb, ranging from 1 to 3 particles per FITC-fluorescent cells [22]. These observations suggest that MIFC can be a useful tool to study in depth the formation of cell aggregates, and their constituents.…”
Section: Multi-cell Clustering and Aggregatesmentioning
confidence: 82%
“…MIFC technology has also been used to study the cellular composition of cell aggregates, as is the case during the formation of rosettes by the adhesion of platelets and leukocytes [22]. CD36 is frequently used as a marker of monocytes, erythrocytes, or platelets in clinical cytometry, while antibodies binding to CD36 may induce platelet activation and formation of platelet's rosettes on leukocytes.…”
Section: Multi-cell Clustering and Aggregatesmentioning
confidence: 99%
See 1 more Smart Citation
“…It has previously been shown that leukocyte-platelet aggregates or coincidence of platelets can interfere with measurement of expression on leukocytes in whole blood (5,6). To our knowledge, the interfering effect of leukocyte-platelet aggregates on leukocyte viability measurement has not yet been studied.…”
Section: Introductionmentioning
confidence: 84%
“…IFC combines the statistical advantage of FC with the ability to identify each event based on a real image, which allows it to analyze protein expression in single cells in heterogeneous cell populations, where the level of expression of one of the proteins is low and could be described by Poisson distribution (rare cell subpopulations with <0.01% of expression). In recent years, IFC was also employed for the evaluation of asymmetric cell division (Filby et al 2011), internalization of CypHer5E-conjugated antibodies and PKH-labeled exosomes (Xu et al 2010;Vallhov et al 2011), intercellular communication by exchange of cytoplasmic material (Domhan et al 2011), analysis of cell interactions and immune synapse (Ahmed et al 2009;Ouk et al 2011), and some other experimental applications (Ponomarev et al 2011). In recent years, IFC was also employed for the evaluation of asymmetric cell division (Filby et al 2011), internalization of CypHer5E-conjugated antibodies and PKH-labeled exosomes (Xu et al 2010;Vallhov et al 2011), intercellular communication by exchange of cytoplasmic material (Domhan et al 2011), analysis of cell interactions and immune synapse (Ahmed et al 2009;Ouk et al 2011), and some other experimental applications (Ponomarev et al 2011).…”
Section: Ifc In the Evaluation Of Cellular Heterogeneitymentioning
confidence: 99%